E-Tourism Sebagai Media Wisata Kabupaten Bekasi Berbasis Website - Wiyanto Wiyanto; Salsa Fadhilah; Arif Siswandi (Journal of Practical Computer Science, 2022)
Bekasi Regency is one of the regencies located in the province of West Java. This district is located just east of Jakarta, bordering the city of Bekasi. Bekasi Regency has many tourist attractions that can be visited. Such as parks, forests, lakes, beaches and others. Bekasi Regency has become one of the areas with very rapid progress and has tourism objects that can increase the regional income of Bekasi Regency. In addition, many local and foreign tourists visit, but only know a few tourist objects because of the lack of information systems in tourism management in Bekasi Regency that have not been managed and developed properly. So it is necessary to develop a tourist information system to make it easier for tourists to visit tourism objects in Bekasi Regency and make it easier to manage promotions. The results of this study are in the form of an E-Tourism system as a website-based tourist information media that makes it easier for tourists to find wizard places in Bekasi Regency. Keywords: E-Tourism, Tourist, Information System, Bekasi Regency.